Number of siblings, birth order, and childhood overweight: a population-based cross-sectional study in Japan - Ochiai Hirotaka; Shirasawa Takako; Ohtsu Tadahiro; Nishimura Rimei; Morimoto Aya; Obuchi Ritsuko; Hoshino Hiromi; Tajima Naoko; Kokaze Akatsuki (BMC, 2012)
Abstract Background Although several studies have investigated the relationship between the number of siblings or birth order and childhood overweight, the results are inconsistent. In addition, little is known about the impact of having older or younger siblings on overweight among elementary schoolchildren. The present population-based study investigated the relationship of the number of siblings and birth order with childhood overweight and evaluated the impact of having younger or older siblings on childhood overweight among elementary schoolchildren in Japan. Methods Subjects comprised fourth-grade schoolchildren (age, 9-10 years) in Ina Town during 1999-2009. Information about subjects' sex, age, birth weight, birth order, number of siblings, lifestyle, and parents' age, height, and weight was collected by a self-administered questionnaire, while measurements of subjects' height and weight were done at school. Childhood overweight was defined according to age- and sex-specific cut-off points proposed by the International Obesity Task Force. A logistic regression model was used to calculate the odds ratio (OR) and 95% confidence intervals (95% CI) of "number of siblings" or "birth order" for overweight. Results Data from 4026 children were analyzed. Only children (OR: 2.13, 95% CI: 1.45-3.14) and youngest children (1.56, 1.13-2.16) significantly increased ORs for overweight compared with middle children. A larger number of siblings decreased the OR for overweight (P for trend < 0.001). Although there was no statistically significant relationship between a larger number of older siblings and overweight, a larger number of younger siblings resulted in a lower OR for overweight (P for trend < 0.001). Conclusions Being an only or youngest child was associated with childhood overweight, and having a larger number of younger siblings was negatively associated with overweight. The present study suggests that public health interventions to prevent childhood overweight need to focus on children from these family backgrounds.